Pemasaran Melalui Media Sosial di TikTok: Apakah Waktu dan Tipe Konten Memengaruhi Tingkat Keviralan? - Arya, Sun Mukti; Wahid, Risqo; Purnamasari, Endah Dewi (Universitas muhammadiyah palembang, 2022)
This study aims to analyze the effects of posting time (i.e., days) and content characteristics on customer engagement (i.e., likes, shares, and comments) on TikTok. The total dataset was 815 posts collected from 9 culinary business accounts which products are on TikTok and offered to Indonesian consumers. Data were collected using content analysis and analyzed using negative binomial regression on SPSS. The results show that posting times and content characteristics have varying effects on likes, shares, and comments on TikTok. This research extends social media marketing and content marketing literatures through the discussion of TikTok as a short-video based social media platform. Practically, insights from this study can assist Indonesian businesses in maximizing the performance of their social media marketing and content marketing strategies.